Homopolyatomic Chalcogen Radical Cations of Selenium and Tellurium. Issue 2 (8th January 2020) - Jenne, Carsten; Nierstenhöfer, Marc C.
Abstract : The stability of selenium and tellurium homopolyatomic radical cations in the gas phase and liquid sulfur dioxide solution was estimated using density functional theory (DFT). First of all, the structures of the neutral, cationic, and dicationic homopolyatomic chalcogen clusters [Ch x ] y + (Ch = Se, Te; x = 3–10, y = 0–2) were optimized in the gas phase. The stability of the currently unknown radical cations [Ch x ] + against various decomposition reactions (e.g. disproportionation, dimerization) was predicted by estimating the reaction enthalpies and free energies in the gas phase and in liquid sulfur dioxide solution applying a solvation model. The solvent SO2 was chosen, because homopolyatomic chalcogen cations react immediately with most common organic solvents but are known to be stable in liquid sulfur dioxide. A significant stability in solution was predicted only for the radical cations [Se5 ] + and [Se8 ] +, while [Te8 ] + is a borderline case. In the course of our investigations the previously unknown dications [Ch5 ] 2+ were calculated as well, which have a triplet rather than a singlet ground state similar to the three‐atomic [S3 ] 2+ dication. Abstract : The structures of the homopolyatomic radical cations of the chalcogen elements selenium and tellurium were optimized by density functional theory calculations. The homopolyatomic radical cations [Se5 ] +, [Se8 ] +, and [Te8 ] + are predicted to be stable in liquid sulfur dioxide solution.